Comparison of Clinical Outcomes Using "Elevate Anterior" versus "Perigee" System Devices for the Treatment of Pelvic Organ Prolapse. (29th March 2015) - Long, Cheng-Yu; Wang, Chiu-Lin; Wu, Ming-Ping; Wu, Chin-Hu; Lin, Kun-Ling; Liu, Cheng-Min; Tsai, Eing-Mei; Shen, Ching-Ju
Abstract : Objective. This study aims to compare clinical outcomes using the Perigee versus Elevate anterior devices for the treatment of pelvic organ prolapse (POP). Study Design. One hundred and forty-one women with POP stages II to IV were scheduled for either Perigee (n = 91 ) or Elevate anterior device (n = 50 ). Preoperative and postoperative assessments included pelvic examination, urodynamic study, and a personal interview about quality of life and urinary symptoms. Results. Despite postoperative point C of Elevate group being significantly deeper than the Perigee group (median: −7.5 versus −6; P < 0.01 ), the 1-year success rates for two groups were comparable (P > 0.05 ). Apart from urgency incontinence, women with advanced POP experienced significant resolution of irritating and obstructive symptoms after both procedures (P < 0.05 ), generating the improvement in postoperative scores of Urogenital Distress Inventory (UDI-6) and Incontinence Impact Questionnaire (IIQ-7) (P < 0.01 ). On urodynamics, only the residual urine decreased significantly following these two procedures (P < 0.05 ). Women undergoing Perigee mesh experienced significantly higher visual analogue scale (VAS) scores and vaginal extrusion rates compared with the Elevate anterior procedure (P < 0.05 ). Conclusions. With comparable success rates, the Elevate procedure has advantages over the Perigee surgery with lower extrusion rate and postoperative day 1 VAS scores.